Penggunaan Monoterapi Vs Kombinasi Terapi Antinyeri Dalam Manajemen Nyeri Pascaoperasi Pediatri : Literatur Review - Ria Wahyu Januarti; Khadafi Irawan (CV. Jasa Sukses Abadi, 2026)
Postoperative pain is an acute sensation accompanied by an inflammatory process related to surgical trauma, which decreases as the tissue heals. However, it is often not well managed after surgery in children. Multimodal analgesia is a key principle for managing acute postoperative pain. One form of multimodal analgesia is combining non-opioid analgesics to reduce postoperative pain and opioid use. The latest guidelines recommend a combination of at least paracetamol and nonsteroidal anti-inflammatory drugs (NSAIDs) for most types of surgery. NSAIDs and paracetamol have different mechanisms of action, so it can be assumed that combining the two will provide better analgesia than either drug alone. This article was written using the literature review method, which involved searching for literature from various national and international journals. Journal articles from 2015 to 2025 were used as the basis for the articles. The literature search references are from the PubMed, NCBI, and Google Scholar databases. The literature was then analyzed using the systematic literature review method, which included activities such as collecting, evaluating, and comparing the efficacy and acute management post-surgery. Hye-Mi et al.'s research found that the combination of NSAIDs with propacetamol is better postoperative analgesia than opioids. Intravenous administration provides a higher maximum plasma concentration (Cmax) and a shorter time to reach Cmax, resulting in faster and more reliable delivery compared to oral or rectal administration.